ASIGURAREA SUBVENŢIONATĂ A RISCURILOR ÎN ACTIVITATEA AGRICOLĂ - Efros, Elena (CEP USM, 2013)
În această lucrare sunt prezentate rezultatele unor cercetări ştiinţifice asupra problemelor cu care se confruntă fermierii din Republica Moldova privind utilizarea corectă a diferitelor tipuri de subvenţii. În concluzie autorul vine cu unele recomandări concretizate în măsuri eficiente pentru susţinerea de către stat a sectorului agricol, ce rezultă din cercetarea experienţei altor ţări în acest domeniu.

In this paper the author presents the results of the scientific research on the problems faced by the farmers in Republic of Moldova concerning the proper use of various forms of subsidies. The conclusions contain some recommendations on the effective measures for the state support of agricultural sector, resulting from the research of the experience of other countries in this field.
SUBVENTIONED INSURANCE OF RISCS IN AGRICULTURAL ACTIVITY
Keywords: subvenţionarea agriculturii; sistemul de subvenţionare; risc agricol; subvenţionare a fermierilor; state insurance programs; agricultural risk; price and income support of farmers